2021
DOI: 10.1007/s43926-021-00008-5
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end experimentation of a 5G vertical within the scope of blended learning

Abstract: The next generation of mobile networks, widely known as 5G, was designed to respond to the next 10 years’ communication challenges. 5G will be an essential structure on which all types of electronic communications will rely. Built on the emerging 5G technology, we developed a vertical solution for blended learning environments within a Portuguese national project scope. The project aims to propose an integrated demonstration of a set of products capable of being part and providing services in the future 5G net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Multisensor network refers to the wireless interconnection and cooperation among many sensor units with communication and computing capabilities and interacts with the external environment to jointly complete a set of specific tasks [ 13 , 14 ]. The multisensor network monitors and collects information about the surrounding external environment through real-time collaborative monitoring.…”
Section: Multisensor Monitoring Methodsmentioning
confidence: 99%
“…Multisensor network refers to the wireless interconnection and cooperation among many sensor units with communication and computing capabilities and interacts with the external environment to jointly complete a set of specific tasks [ 13 , 14 ]. The multisensor network monitors and collects information about the surrounding external environment through real-time collaborative monitoring.…”
Section: Multisensor Monitoring Methodsmentioning
confidence: 99%
“…All of this component analysis and their integration create interest among students to have better experiences and give comparatively improved performances. Armando et al [73] studied the blended learning environment from the project learning environment perspective. Here, an emerging 5G technology-based project for a Portuguese nation is considered.…”
Section: A Models Of Blended Learningmentioning
confidence: 99%
“…Figure 5 depicts the basic framework of blended learning components and associated emerging technologies. Armando et al [73] discussed about the concept of 5GOpenClass for the technology era of 2020 and future that enhances the blended learning model. 5GOpenClass incorporates high-definition video streaming, Internet of things (IoT) as part of teaching learning process, where the teacher and learners can perform live streaming of class videos, multimedia-based learning materials repository, interactive live video chats, and whiteboards.…”
Section: B Processes Of Elearning and Blended Learning Adopted In Past And Presentmentioning
confidence: 99%
“…BL increases student participation from eight indicators: visual, oral, writing, writing, drawing, metrics, mental, and emotional skills [7]. Armando et al [25] designed an innovative location-based service for BL environments with 5G technology. Engelbertink et al [26] found that the participatory design approach to leading BL course is the use of technology that focuses on content, target group, context, and ethical aspects in the course.…”
Section: Literature Reviewmentioning
confidence: 99%